Peran Platform Digital dalam Meningkatkan Daya Saing Produk Kosmetik Wardah Syariah Melalui Pemasaran Digital - Naisa Qori'a Sani; Zelika Salsa Kayla; Ristia Khairatunisa; Maya Panorama (Pusat Riset dan Inovasi Nasional, 2025)
This study focuses on the role of digital platforms in increasing the competitiveness of Wardah cosmetic products through digital marketing. With the rapid growth of the beauty industry in Indonesia, Wardah, as a halal cosmetic brand founded in 1995, emphasizes products that are in line with Islamic principles. Through creative marketing strategies and the use of social media, Wardah is able to reach a wider audience, especially among the younger generation. This study also highlights the quality of Wardah products used as halal labels, and prices on customer satisfaction and loyalty. This analysis shows that effective digital marketing can attract consumer interest and strengthen Wardah's position in the market. And it is hoped that the results of this study can provide guidance for the development of more optimal marketing strategies in the cosmetics industry.